Environmental and Social Management Plan (ESMP) for the Pilot of Climate-Smart Agricultural Innovations and Climate Information Services Technologies in Kenya - International Livestock Research Institute (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This Environment and Social Management Pan (ESMP) has been developed to clarify (i) the measures that will be taken during the implementation of project activities to eliminate or offset adverse E&S impacts, or to reduce them to acceptable levels; and (ii) actions needed to implement these measures during the implementation of the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project activities in Kenya during the Additional Financing (AF). The purpose of this ESMP is to consider and develop proper measures to decrease the possibility of environmental degradation during all phases of the project AF, and to provide clearly defined action plans and emergency response procedures to account for human and environmental health and safety in accordance with the requirements of kenyan laws and the objectives of the World Bank Environmental and Social Standards (ESS) : ESS-1: Assessment and Management of Environmental and Social Risks and Impacts ESS-2: Labor and Working Conditions ESS-3: Resource Efficiency and Pollution Prevention and Management ESS-4: Community Health and Safety ESS-6: Biodiversity Conservation and Sustainable Management of Living Natural Resources. The ESMP will cover the additional phase of the Project. It is a living document, which will be updated and re-disclosed as and when new risks are identified, or field activities are expanded.